Exercise self-efficacy remains unaltered during military service - Kekäläinen, Tiia; Pulkka, Antti-Tuomas; Kyröläinen, Heikki; Ojanen, Tommi; Helén, Joonas; Pihlainen, Kai; Heikkinen, Risto; Vaara, Jani P. (Frontiers in Psychology, 2024)
Background: Exercise self-efficacy is a crucial aspect of adopting and maintaining a physically active lifestyle. Regular physical activity may enhance exercise self-efficacy. This study aimed to investigate the baseline associations of physical fitness, physical activity, and body composition with exercise self-efficacy and the effects of military service on exercise self-efficacy. Methods: The sample consisted of healthy young Finnish conscripts (n=243) undergoing military service. The participants were divided into two groups: an intervention group undergoing a high-intensity functional training program (n=113) and a control group undergoing traditional physical training within their military service (n=130). Exercise self-efficacy (adoption and barrier) and aerobic and muscular fitness were measured thrice (baseline, month 3, and month 5). Self-reported leisure-time physical activity and measured fat percentage were collected at baseline. Results: Adoption and barrier exercise self-efficacy correlated positively with aerobic and muscular fitness and leisure time physical activity (r=0.33–0.59, p<0.001), and barrier self-efficacy negatively with fat percentage (r=-0.15, p<0.05) at baseline. No changes in adoption (time p=0.912) and barrier self-efficacy (time p=0.441) occurred during the military service. There were no differences between groups in these changes (group × time interaction p=0.643 for adoption self-efficacy and p=0.872 for barrier self-efficacy). Change in muscular fitness correlated positively with change in barrier self-efficacy in the high-intensity functional training group (r=0.35, p<0.05). Conclusions: Exercise self-efficacy is positively associated with physical fitness and physical activity among young males. However, military service, whether it involves high-intensity functional physical training or more diverse traditional physical training, does not improve exercise self-efficacy.